Integrating Blue and Green Economy Philanthropy into Eco-Pedagogy: A Strategic Framework for Strengthening Village SDGs and K-12 Digital Resilience - Yusuf, Yusuf; Misbah, Hanim (Jurnal Pendidikan Anak, 2026)
The rapid transition toward a sustainable global economy necessitates a fundamental shift in K-12 education, particularly in integrating environmental ethics with digital literacy. This research evaluates how Blue and Green Economy philanthropy can be strategically integrated into eco-pedagogy to strengthen Village SDGs and foster digital resilience among students (Ages 7-18). Utilizing a Systematic Literature Review (SLR) and content analysis of high-impact publications (2020-2025), this study proposes a novel "Interdisciplinary Sustainability Framework" (ISF). The findings indicate that philanthropy-driven eco-pedagogy, when integrated through digital-based environmental monitoring apps, social-media-driven climate campaigns, and VR/AR immersive learning environments, significantly enhances students' digital resilience and critical inquiry. The results highlight that teacher-led scaffolding is the most dominant variable in successful implementation, while infrastructure-only philanthropy without pedagogical integration shows minimal impact on character resilience. This study implies that for Village SDGs to be sustainable, philanthropic investments must prioritize the synergy between eco-literacy and digital ethics, funded through sustainable tech grants, within rural educational settings.